Porous monoliths synthesized via polymerization of styrene and divinyl benzene in nonaqueous deep-eutectic solvent-based HIPEs. Issue 30 (2nd March 2015) - Pérez-García, M. G.; Carranza, A.; Puig, J. E.; Pojman, J. A.; del Monte, F.; Luna-Bárcenas, G.; Mota-Morales, J. D.
Abstract : Due to their viscosity and polarity, DESs represent a suitable internal phase for HIPEs containing styrenic monomers in addition to acrylates, thus expanding on the range of monomers forming polymerizable DES-based HIPEs. Abstract : Stable nonaqueous high internal phase emulsions (HIPEs) were prepared and thermally polymerized to yield poly(HIPEs). The internal phase accounting for 80 vol% of the HIPE consisted of a deep-eutectic solvent (DES) while the continuous one comprised styrene and divinyl benzene in a 10 : 1 molar ratio. DESs with different viscosities were used as an internal phase: choline chloride combined with urea, glycerol or ethylene glycol in a 1 : 2, salt : hydrogen bond donor molar ratio, respectively. HIPEs were stabilized with different amounts of the surfactant Span 60 (10, 20 and 50 wt% with respect to the total amount of monomers). DESs viscosity and the amount of surfactant employed impact the morphology and mechanical properties of poly(HIPEs). Resulting poly(HIPEs) showed interconnected porosity and high thermal stability above 310 °C. It's worth noting that DES was recovered from 89 to nearly 95 wt% and the monomer conversion was as high as 0.96. In addition, water-in-oil HIPEs were stabilized and then polymerized under the same conditions, but the porous structure of the resulting poly(HIPEs) collapsed. This research demonstrates that DESs are a suitable internal phase for HIPEs thus expanding on the range of monomers forming polymerizable DES-based HIPEs.